2020
DOI: 10.1093/biolre/ioaa226
|View full text |Cite
|
Sign up to set email alerts
|

Conceptus-induced, interferon tau-dependent gene expression in bovine endometrial epithelial and stromal cells†

Abstract: Bovine endometrium consists of epithelial and stromal cells that respond to conceptus interferon tau (IFNT), the maternal recognition of pregnancy (MRP) signal, by increasing expression of IFN-stimulated genes (ISGs). Endometrial epithelial and stromal-cell-specific ISGs are largely unknown but hypothesized to have essential functions during pregnancy establishment. Bovine endometrial epithelial cells were cultured in inserts above stromal fibroblast (SF) cells for 6 h in medium alone or with IFNT. The epithel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 120 publications
0
15
0
Order By: Relevance
“…By comparing the previously reported transcriptome analysis with the DEGs in our study, we observed that few genes were uniformly regulated by IFNT between EECs and in vivo uteri. In the co-culture system of bovine EECs and stromal cells, the authors identified 222 upregulated DEGs in bovine EECs by comparing IFNT-treated and untreated groups; of which 96 of 222 appeared in our DEG list and all showed upregulation (22). We also compared our data with the DEGs in the receptive uterus vs. unreceptive uterus reported by Zhang et al (23), because there are few reports on the transcriptome of IFNTtreated cells.…”
Section: Discussionmentioning
confidence: 95%
“…By comparing the previously reported transcriptome analysis with the DEGs in our study, we observed that few genes were uniformly regulated by IFNT between EECs and in vivo uteri. In the co-culture system of bovine EECs and stromal cells, the authors identified 222 upregulated DEGs in bovine EECs by comparing IFNT-treated and untreated groups; of which 96 of 222 appeared in our DEG list and all showed upregulation (22). We also compared our data with the DEGs in the receptive uterus vs. unreceptive uterus reported by Zhang et al (23), because there are few reports on the transcriptome of IFNTtreated cells.…”
Section: Discussionmentioning
confidence: 95%
“…In addition to these chemokines, IFNT induces the expression of numerous interferon-stimulated genes (ISGs) in the maternal uterus [ 83 , 84 , 85 ]. Although the detection of ISGs expression in the uterus is well documented [ 85 , 86 , 87 ], elevated ISGs expression has been reported in various tissues other than the uterus, such as blood cells, luteal tissue, and liver during pregnancy [ 88 , 89 , 90 , 91 , 92 , 93 , 94 ].…”
Section: Common Maternal Responses Exist During the Early Mid-pregnan...mentioning
confidence: 99%
“…The bovine endometrial epithelium cells (BEnEpC) are the first line of defense in exposure to various invading agents [21]. BEnEpC are often used as a bovine in vitro model for studying the biological characteristics, cellular and molecular mechanisms, development of interactions between the embryo and mother, and responses to infection or damage of the bovine uterine epithelium [22][23][24][25][26]. However, the consequences of antiseptics on BEnEpC have not been described.…”
Section: Introductionmentioning
confidence: 99%